2013
DOI: 10.1002/ajmg.a.35790
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Germline Mosaicism for a Novel 19p13.13 Deletion Disrupting NFIX and CACNA1A

Abstract: We report on a case of apparent germline mosaicism in a family of two sisters carrying a novel 19p13.13 deletion. The 11-year-old proposita was referred for evaluation of macrocephaly, moderate intellectual disability (ID), and episodic ataxia. Array comparative genomic hybridization (CGH) detected a 399 kb microdeletion with breakpoints within genes NFIX and CACNA1A. A similar deletion was also seen in the elder sibling who presented with macrocephaly, ID, and strabismus. The deletions were confirmed to be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 15 publications
(37 reference statements)
0
33
0
Order By: Relevance
“…In one family, there was presumed gonadal mosaicism. 9 Yoneda et al 6 reported one child with a missense substitution in the DNA-binding domain which had been inherited from a possibly affected mother (c.362G4C, p.(Arg121Pro)); Supplementary Table 2). Although the location and physicochemical properties of this variant and the description of the facial and other phenotypic features of this child are consistent with its pathogenicity, caution is required in the interpretation of missense variants in NFIX, particularly when they are inherited.…”
Section: Molecular Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one family, there was presumed gonadal mosaicism. 9 Yoneda et al 6 reported one child with a missense substitution in the DNA-binding domain which had been inherited from a possibly affected mother (c.362G4C, p.(Arg121Pro)); Supplementary Table 2). Although the location and physicochemical properties of this variant and the description of the facial and other phenotypic features of this child are consistent with its pathogenicity, caution is required in the interpretation of missense variants in NFIX, particularly when they are inherited.…”
Section: Molecular Resultsmentioning
confidence: 99%
“…A variety of variant types have been seen in association with the Sotos-like phenotype, including whole gene deletions (10 patients), one nonsense variant and missense variants and in-frame deletions affecting the DNA-binding domain (3 patients). [4][5][6][7][8][9][10] Five of the reported NFIX deletions also encompass the nearby CACNA1A gene, haploinsufficiency of which causes episodic ataxia type 2 or familial hemiplegic migraine.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive and behavioral impairments have been reported in a minority of patients with CACNA1A mutations, including in two children with sporadic epileptic encephalopathies, 17,18 in six children with EA2 and ID, [19][20][21][22] including two siblings with a 19p13.13 deletion. 23 Rare cases of FHM1 with ID 24 and progressive cognitive decline [24][25][26] have been reported. Therefore, our data together with previous reports suggest that children with global DD, ID or ASD with mild cerebellar symptoms, with or without a family history suggestive of EA2, should be investigated for loss-of-function mutations in the CACNA1A gene.…”
Section: Discussionmentioning
confidence: 99%
“…He had early-onset thoracic aortic aneurysm with mild aortic regurgitation and developed thoracic aortic dissection at the age of 38 years. Although a mildly dilated aortic root at the sinus of Valsalva was previously reported in an 11-year-old Caucasian American girl who was carrying a 19p13.13 deletion disrupting NFIX and CACNA1A , 7 there have been no published cases complicated with aortic dissection in patients with Sotos-like phenotypes. Our patient is the oldest reported patient with NFIX mutations, and thoracic aortic aneurysm and dissection (TAAD) deserve particular attention in relatively long-lived patients with Sotos-like phenotypes.…”
mentioning
confidence: 95%
“…Nimmakayalu et al previously reported an 11-year-old Caucasian American girl with a 19p13.13 deletion that disrupted NFIX and CACNA1A due to parental germline mosaicism and led to macrocephaly, intellectual disability, episodic ataxia, and a mildly dilated aortic root at the sinus of Valsalva (29 mm; Z -score=3.4). 7 In contrast, the elder sister aged 16 years with the same chromosome deletion had macrocephaly and intellectual disability but no aortic dilatation. Among 33 previously reported young patients with Malan syndrome (age 1–27 years), TAADs have not been yet reported, and thus, our case is the oldest case and the second case of aortopathy among patients with NFIX mutation-related Sotos-like syndrome.…”
mentioning
confidence: 97%